The Influence of Customer Factors (Preferences, Desires-Demand) on Antenatal Care Services and Delivery Places in Balikpapan City - Mardiana, Nina; Murti, Ni Nyoman; Palin , Yona (Poltekkes Kemenkes Palu, 2024)
Maternal and infant mortality rates remain high in Indonesia, necessitating improvements in health services, particularly for pregnant women. This study aimed to determine the influence of customer factors (preferences, desires, and demands) on antenatal care services and delivery location. A cross-sectional survey was conducted with a sample of 210 mothers who had given birth in Balikpapan City, selected using multistage random sampling. Data were collected using questionnaires and analyzed descriptively, examining relationships between variables and using Partial Least Square (PLS) analysis. Results showed that customer factors significantly influenced antenatal care services (coefficient=0.454, t>t-table) and choice of delivery location (coefficient=0.434, t>t-table). Preferences for antenatal care were highest for independent midwives (35.2%) and hospitals (35.2%), while desires for delivery location were highest for hospitals (57.2%). The majority of respondents (73.7%) had their first antenatal check-up in the first trimester, and 76.2% had more than four check-ups. The most common delivery locations were hospitals (46.7%) and health centers (38.1%). In conclusion, an increase in customer factors (preferences, desires, and demands) was found to increase antenatal care service utilization by 45.4% and influence the choice of delivery location by 43.4%.